Theoretical innovations of Zenonas Ivinskis - Bumblauskas, Alfredas (Lietuvos istorijos studijos, 1997)
Theoretical innovations of Zenonas IvinskisThe article deals with the theoretical attitudes and research methods of the most prominent interwar and exile Lithuanian historian Zenonas Ivinskis. It is an attempt to apply, for the first time, the methodology of John Rüsen, a German theoretician, i. e. to perceive an interaction of pragmatism, historism, and Überwindung des Historismus (overcoming of historism) for the analysis of Lithuanian historiography. The criticism of pragmatism and the substantiation of historism are clear in his scientific heritage; he devoted special works to the theoretical problems and the analysis of the development of historiography. It is true that Zenonas Ivinskis did not discuss the character of the historistic methodology; one must reconstruct his attitudes from his specific historical studies. Two main conclusions can be drawn: 1) he did not accept the “inventory of events” in historism and noticed the absence of discussion on the programs of historical research as well as the predetermination of events based on the assumption of statehood as an arranged principle in historical synthesis. 2) Zenonas Ivinskis tried to refuse the narrative or “cut and paste” method (concept of T. J. Collingwood). An attempt was made to introduce an active relation between the researcher and historical sources; this is called “problemical historism” in the article.Nevertheless, Zenonas Ivinskis’ scientific works do not fit into the framework of historism, which was predominant in Germany (where he studied and defended his doctoral thesis). Universalities of the Lithuanian geopolitical history were offered in some of his works. Also, he presented a new chronological division of the history of Lithuania based on the peasants' relations with the land (which can be treated as an insight of structural history). Zenonas Ivinskis also started to shape a new understanding of Lithuanian cultural history which challenged the speculative theoretical patterns. His most significant theoretical innovation was to typologize, for the first time in Lithuanian historiography, the processes of Lithuanian history, confronting them with Western Europe. This can also be treated as a clear sign of the new paradigm - Überwindung des Historismus (overcoming of historism).
Keywords: -